Pengaruh Kegiatan Ekstrakulikuler Muhaḍarah terhadap Penguatan Aspek Kognitif Santri di Pondok Pesantren Daarul Rahman III - Fayakun, Umar Kun; M., Nur Afif; Qowim, Agus Nur (Ikatan Dai Indonesia, 2023)
This study aims to determine how much influence the Muha'arah Extracurricular Activities have on Strengthening the Cognitive Aspects of Santri at Daarul Rahman III Islamic Boarding School. In this study the authors use quantitative research, namely analyzing the data obtained from the results of research in the form of data and information related to the title to be studied. The data obtained by the author through the distribution of questionnaires, documentation, observations and interviews. In analyzing the data, the writer uses editing, scoring, data tabulation, data display, conclusing drawing/verification. The population in this study were students of class IX A Pondok Pesantren Daarul Rahman III who were taken randomly, amounting to 39 students. The results of this study indicate that the calculated r value is 0.645 and is included in the strong category. With a coefficient of determination (KD) of 41.7%. Thus this understanding proves that there is a positive influence between muha'arah extracurricular activities on strengthening the cognitive aspects of students at Daarul Rahman III Islamic Boarding School.